O impacto do "Debriefing" no atendimento da parada cardiorrespiratória no SAMU - Faria, Elaine Boreli Gianini de (2024)
victims treated by the Advanced Life Support Units of the São José do Rio Preto Mobile Emergency Care Service. METHODS: Cross-sectional study with a descriptive design and quantitative analytical approach, in which the population was made up of the care records of all patients who were victims of cardiorespiratory arrest, treated in the city of São José do Rio Preto -SP, by Advanced Life Support of the Mobile Emergency Care Service, from January 2020 to December 2022. The Student's t-test and Classical Chi-square test were used for statistical analysis. The variables used were age, gender, month and year of occurrence, patient destination, outcome of care, and response time. The exclusion criteria were incorrect or partial completion of data in the care or debriefing form and failure to confirm a cardiorespiratory arrest by the team upon arriving at the scene. RESULTS: A total of 404 patients were treated, with a predominance of male victims, aged 61 to 70 years (23,8%). The average time from receiving the call to the team's arrival at the scene was 18 minutes and 54 seconds; nine minutes from receiving the call to deploying the resource; 42 seconds from the team's departure and nine minutes and 12 seconds from deploying the resource to arriving at the incident scene The reversal of Cardiorespiratory Arrest occurred in 20.5% of consultations, with Santa Casa de Misericórdia (9,9%) being the main reference for these victims. Debriefing was carried out in 50.5% of the cases treated, that is, 204 patients, and of these, the reversal rate was 24.01%. In the year the debriefing was implemented, in 2020, the reversal rate was 10.5%, in 2021, it was 21.7% and in 2022, 33.7%. CONCLUSION: After the implementation of the debriefing in 2020, a progressive and consistent increase was observed in the reversal rates of cardiorespiratory arrests in the care provided by the São José do Rio Preto Mobile Care Service teams, which highlights the significant and effective impact of this strategy. Debriefing directly contributes to the technical improvement of teams working in emergency services, promoting more assertive and agile interventions in critical situations. This continuous improvement not only directly benefits the patients' assistance, but also strengthens the health system as a whole, resulting in higher quality and safer care for society, reaffirming the commitment to excellence in emergency care.